Cone-beam Computed Tomography Evaluation Timings of Closure of Open Apex by Using Deciduous Tooth Pulp Autotransplantation for the Regenerative Endodontic Treatment of Permanent Teeth with Pulp Necrosis - Abhinandan Patra; Sonal Gupta; Rohan Shrivastava; Sheenam Ayub; Meghali Langthasa (Contemporary Clinical Dentistry, 2024)
Regenerative endodontic therapy (RET) of young permanent teeth with necrotic pulps and apical periodontitis in young people, deciduous tooth pulp may be utilized as a natural, biologic scaffold. Recent developments in stem cell biology and material sciences are beneficial for new treatment methods. Previously traumatized and necrotic young permanent tooth was treated with RET protocol. In the first visit, irrigation, and placement of triple antibiotic paste dressing were done. After that in the second visit, intracanal medication was removed and whole pulp tissue harvested from the deciduous tooth was transplanted in the young permanent tooth. Following placement of Biodentine® coronal barrier, access cavity was restored with acid-etch resin composite. This case report would highlight favorable outcome of RET using deciduous pulp autotransplantation in young permanent tooth using cone-beam computed tomography for 6 months’ follow-up.